Nurcholish Madjid’s Perspective About Thought of Religious Pluralism - Dian Dian; Imas Masripah; Dela Purwandani; Deagi Nur Mohamad Maliki; Fadhilah Anggraini Pane (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2022)
One of the modern Islamic reformers in Indonesia is Nurcholish Madjid. The focus of this research is to find out the style of thought of Nurcholis Madjid regarding religious pluralism. The aims of this study are to (1) describe the style of Nurcholis Madjid’s thought related to religious pluralism, (2) open new insights regarding modern Islamic views, and (3) describe the contributions and controversies of Nurcholis Madjid’s thoughts regarding religious pluralism. This study uses a descriptive-comparative research approach. The results of this study indicate that there are three thoughts of Nurcholis Madjid about religious pluralism. First, according to him, religious pluralism is an understanding that recognizes the existence of other religions and is mature in dealing with diversity. Second, Nurcholish Madjid's idea of religious pluralism is a religious principle that recognizes freedom of religion, living with risks that will be borne by each believer. Third, according to Nurcholish Madjid, religious pluralism in Islam is not based on the doctrine of assuming that all religions are true, but Islam only gives recognition to the extent of each individual's right to exist in harmony with the freedom to practice their respective religions to realize a tolerant life in Indonesia.